Pembelajaran Motorik Berbasis Permainan untuk Meningkatkan Koordinasi Mata-Tangan dan Keterampilan Motorik Dasar Murid SDN 1 Kepanjen Jombang - Lucky Wijaya; Muchamad Arif Al Ardha; Junaidi Budi Prihanto (MAN Insan Cendekia Jambi, 2026)
Basic motor skill instruction at the elementary school level plays a crucial role in establishing the foundation for movement skills, body coordination, and student self-confidence. However, a lack of instructional variety and the dominance of conventional, command-based teaching methods often limit students' exposure to diverse movement activities; consequently, many students struggle to master basic motor skills and movement coordination. This study aims to analyze the effectiveness of implementing a game-based motor learning model on improving hand-eye coordination and basic motor skills among elementary school students. This quantitative study employed a quasi-experimental approach using a pretest-posttest control group design. The sample consisted of 50 students from SDN Kepanjen 1 Jombang, selected via total sampling and evenly divided into an experimental group (n=25), which received game-based instruction and a control group (n=25), which underwent conventional instruction. Data collection instruments included the wall toss test to measure hand-eye coordination and the Test of Gross Motor Development-2 (TGMD-2) to assess basic motor skills. Data analysis involved descriptive statistics, prerequisite tests (Shapiro-Wilk normality test and Levene’s homogeneity test), paired sample t-tests, and independent sample t-tests. The results showed that the experimental group’s mean score increased from 67.12 in the pretest to 83.84 in the posttest, while the control group’s score rose from 66.88 to 77.48. The paired sample t-test demonstrated a significant improvement in the experimental group (t = -13.116; p = 0.000 < 0.05). Furthermore, the independent sample t-test confirmed a significant difference in learning outcome improvements between the two groups (p = 0.000 < 0.05), with the experimental group recording a substantially greater increase in movement competence compared to the control group. In conclusion, the game-based motor learning model has proven to be significantly effective and can serve as an adaptive alternative approach for improving hand-eye coordination and gross motor skills among elementary school students.